Induction of somatic embryogenesis in Brassica juncea L. and analysis of regenerants using ISSR-PCR and flow cytometer - Faisal, Mohammad (Saudi J Biol Sci, 2021)
A new and simple protocol has been developed and standardized for direct somatic embryogenesis and plant regeneration from aseptic seedlings derived from immature Brassica juncea seeds. Depending on the age of immature seeds and nutrient media, in vitro occurrence of embryogenesis and the number of embryos from each seedling have varied greatly. The largest number of somatic embryos, producing 12.7 embryos per seedlings, have been developed by seedlings obtained from immature seeds collected after 21 days of pollination (DAP). Effect of different nutrient media [Gamborg (B5), Murashige and Skoog (MS) and Linsmaier and Skoog (SH)] and carbon sources (fructose, glucose, maltose and sucrose) were assessed to induce somatic embryos and the maximum response were achieved on Nitsch culture medium fortified with sucrose (3% w/v) followed by fructose and maltose. The somatic embryo converted into complete plantlets within 04-weeks of culture on Nitsch medium containing half-strength of micro and macro salts. The regenerated plantlets were successfully established in soil with 90% survival rate. The acclimated plants were subsequently transferred to field condition where they grew normally without any phenotypic differences. Genetic stability of B. juncea plants regenerated from somatic embryos were confirmed by inter-simple sequence repeat (ISSR)-PCR analysis and flow cytometry. No significant difference in ploidy level and ISSR banding pattern were documented between somatic embryo’s plants and control plants grown ex vitro.